Case Report: Ectopic Cushing’s syndrome caused by a pancreatic neuroendocrine tumor managed through dual steroidogenesis inhibition and endoscopic ultrasound-guided ethanol ablation - Krzystek, Łukasz; Sagan, Karol P.; Andrysiak-Mamos, Elżbieta; Retfiński, Szymon; Buć, Karolina; Marczak, Wiktoria; Brzeska, Anna; Patalong-Wójcik, Martyna; Żochowska, Ewa; Dąbkowski, Krzysztof; Syrenicz, Anhelli (Frontiers in Endocrinology, 2025)
Ectopic adrenocorticotropic hormone (ACTH)-dependent Cushing’s syndrome (EAS) is a rare complication of neuroendocrine tumors (NETs). Severe hypercortisolism (SH) requires urgent medical intervention due to its life-threatening consequences. We report a 74-year-old female patient with an ACTH-secreting pancreatic NET (pNET) who presented with rapidly progressive cognitive decline, muscle weakness, severe hypokalemia, and hyperglycemia. Laboratory evaluation confirmed ACTH-dependent Cushing’s syndrome with loss of diurnal cortisol rhythm and panhypopituitarism. Surgical treatment was contraindicated because of significant comorbidities. The initial management included intravenous etomidate infusion. Subsequently, osilodrostat was introduced as long-term oral therapy. Marked clinical and hormonal improvements were observed, including the normalization of potassium and cortisol levels, resolution of neuropsychiatric symptoms, and restoration of mobility. After 19 months of osilodrostat therapy, endoscopic ultrasound-guided ethanol ablation of the pancreatic lesion was performed, and medical therapy was discontinued. This case demonstrates the effectiveness of dual steroidogenesis blockade with etomidate and osilodrostat in both the acute and chronic management of severe ectopic Cushing’s syndrome due to pNET. It also highlights the role of endoscopic ethanol ablation as a minimally invasive curative option for patients who are unfit for surgery.